Brain Energy Metabolism in Two States of Mind Measured by Phosphorous Magnetic Resonance Spectroscopy - Galijašević, Malik; Steiger, Ruth; Regodić, Milovan; Waibel, Michaela; Sommer, Patrick Julian David; Grams, Astrid Ellen; Singewald, Nicolas; Gizewski, Elke Ruth (Frontiers in Human Neuroscience, 2021)
Introduction: Various functional neuroimaging studies helped to better understand the changes in brain activity during meditation. The purpose of our study was to investigate how brain energy metabolism changes during focused attention meditation state, measured by phosphorous magnetic resonance spectroscopy (31P-MRS). Methods: 31P-MRS imaging was done in 27 participants after 7 weeks of focused attention meditation training. Metabolite ratios as well as the absolute values of metabolites were assessed after meditation training in two MRI measurements, comparing effects during a focused attention meditation state with those in a distinct focused attention awake state during a backwards counting task. Results: Our results show decreased PCr/ATP, PCr/Pi, and intracellular pH values in entire brain, but especially in basal ganglia, frontal lobes, and occipital lobes, and increased Pi/ATP ratio, cerebral Mg, as well as Pi absolute values were found in the same areas during focused attention meditation compared to the control focused attention awake state. Conclusion: This study used $^3^1$P-MRS in direct assessment of metabolites, and not only their ratios during focused attention meditation state in comparison to focused attention on counting (focused attention awake state). Our results indicate an existence of a higher energetic state during meditation even in short-term meditators.